MicroRNA-29b Suppresses Inflammation and Protects Blood-Brain Barrier Integrity in Ischemic Stroke. (23rd August 2022) - Ma, Xiaoqing; Yun, Ho Jun; Elkin, Kenneth; Guo, Yunliang; Ding, Yuchuan; Li, Guangwen
Abstract : Objectives . Following cerebral ischemia, microRNA- (miR-) 29b in circulating blood is downregulated. This study investigates the underlying mechanism and implications of miR-29b in leukocyte induction. Methods . miR-29b from stroke patients and rats with middle cerebral artery occlusion (MCAO) were assessed using real-time polymerase chain reaction (PCR). miR-29b agomir was used to increase miR-29b expression in leukocytes via intravenous injection. C1q and tumor necrosis factor (C1QTNF) 6, interleukin- (IL-) 1 β, zonula occludens- (ZO-) 1, occludin, and ischemic outcomes were assessed in MCAO rats. Additionally, hCMEC/D3 cells were subjected to oxygen–glucose deprivation (OGD) and cocultured with HL-60 cells. Results . miR-29b levels in neutrophils were found to be significantly lower in stroke patients compared with healthy controls, which may indicate its high diagnostic sensitivity and specificity for stroke. Moreover, miR-29b levels in leukocytes showed a negative correlation with National Institute of Health Stroke Scale (NIHSS) scores and C1QTNF6 levels. In MCAO rats, miR-29b overexpression reduced brain infarct volume and brain edema, decreasing IL-1 β levels in leukocytes and in the brain 24 hours poststroke. miR-29b attenuated IL-1 β expression via C1QTNF6 inhibition, leading to decreased blood-brain barrier (BBB) disruption and leukocyte infiltration. Moreover, miR-29b overexpression in HL-60 cells downregulated OGD-induced hCMEC/D3 cell apoptosis and increased ZO-1 and occludin levels in vitro. Conclusion . Leukocytic miR-29b attenuates inflammatory response by augmenting BBB integrity through C1QTNF6, suggesting a novel miR-29b-based therapeutic therapy for ischemic stroke.